Sleep quality and endometriosis: A group comparison study. Issue 2 (June 2020) - Davie, Stacey; Hamilton, Yasu; Webb, Lachlan; Amoako, Akwasi A
Introduction: Endometriosis affects around 10% of women of reproductive age with symptoms of pelvic pain, dysmenorrhoea, dyspareunia, dyschezia, and infertility. Current research highlights a possible relationship between endometriosis and poor sleep quality. The aim of this study was to assess the relationship between sleep quality and endometriosis. Outcomes measured included sleep quality and quality of life and pain score. Methods: Thirty women with a histological diagnosis of endometriosis and 30 control patients completed an online questionnaire that assessed sleep quality (Pittsburgh Sleep Quality Index) and quality of life (WHO-QOL-BREF). Pain scores within the endometriosis group were evaluated using a visual analogue scale. Results: Women with endometriosis had significantly poorer sleep quality (80% vs 50%, p = 0.015) and lower quality of life scores when compared to the control group. Within the endometriosis group, there were trends between poor sleep, a reduced quality of life, and higher pain scores; however, these did not reach statistical significance. Discussion: Sleep quality and quality of life were significantly reduced in women with endometriosis when compared to controls.